The prediction role of TIMI score in correlation with coronary angiogram to determine the coronary artery disease severity and extent in patients presenting with Non-ST Elevation Acute Coronary Syndrome - S Hussein, Mustafa; H Ibrahim, Sabah (Diyala Journal of Medicine, 2022)
Background: Accurate risk stratification in patient clinically presented as a case of Non-ST Elevation acute coronary syndrome (NSTE-ACS) is important to assess the prognosis as well as to estimate the possible adverse event especially in those patient who are at high risk. Of these scoring risk; Thrombolysis In Myocardial Infarction (TIMI) risk score have been well corroborated to predict the possible prognosis for patients with NSTE-ACS. However, their value in estimation the severity of coronary artery disease (CAD) has been less studied. Objective: To determine the role of TIMI score in prediction the severity of CAD and its extent by correlate the TIMI score with coronary angiography in patients have NSTE-ACS. Patients and Methods: A cross section study, conducted on 264 successive patients admitted with Non-ST Elevation acute coronary syndrome at Ibn-Albitar cardiac center, Baghdad, Iraq, from the 1st of October 2017 to the 1st of October 2018. Patients were rearranging into three groups according to the seven standard variables of TIMI score. The extent of CAD was examined on coronary angiography; a lesion defined significant if stenosis ≥70% in any artery of three major coronary arteries or ≥50% of left main coronary artery. Results: The total number of was 246 patients, mean age was 62.5±2.3 years. There were 67 (27.2%) of them belong to group 1 (low risk group), 142 (57.7%) of them belong to group 2 (intermediate risk group), and 37 (15.1%) of them belong to group 3 (high risk group). 54.1% of patients in group 3 had significant three-vessels coronary artery disease on comparing with 17.6% of group 2 patients and only 7.5% of group 1 patients had these lesions on coronary angiography (P-value <0.01). On the other hand, one-vessel coronary artery disease occurs more commonly and significant statistically (P-value <0.01) in group 2 (31.7%) than in patients in group 1 (26.9%) and group 3 (10.8%). Conclusion: High TIMI risk score patients were more probably to have significant multi-vessels coronary lesions in comparison with those with TIMI risk score in intermediate or low range which lead to help in stratify the risk and possibility of early intervention.